Challenges and opportunities for advancing patient-centered clinical decision support: findings from a horizon scan. (9th May 2022) - Dullabh, Prashila; Sandberg, Shana F; Heaney-Huls, Krysta; Hovey, Lauren S; Lobach, David F; Boxwala, Aziz; Desai, Priyanka J; Berliner, Elise; Dymek, Chris; Harrison, Michael I; Swiger, James; Sittig, Dean F
Abstract: Objective: We conducted a horizon scan to (1) identify challenges in patient-centered clinical decision support (PC CDS) and (2) identify future directions for PC CDS. Materials and Methods: We engaged a technical expert panel, conducted a scoping literature review, and interviewed key informants. We qualitatively analyzed literature and interview transcripts, mapping findings to the 4 phases for translating evidence into PC CDS interventions (Prioritizing, Authoring, Implementing, and Measuring) and to external factors. Results: We identified 12 challenges for PC CDS development. Lack of patient input was identified as a critical challenge. The key informants noted that patient input is critical to prioritizing topics for PC CDS and to ensuring that CDS aligns with patients' routine behaviors. Lack of patient-centered terminology standards was viewed as a challenge in authoring PC CDS. We found a dearth of CDS studies that measured clinical outcomes, creating significant gaps in our understanding of PC CDS' impact. Across all phases of CDS development, there is a lack of patient and provider trust and limited attention to patients' and providers' concerns. Discussion: These challenges suggest opportunities for advancing PC CDS. There are opportunities to develop industry-wide practices and standards to increase transparency, standardize terminologies, and incorporate patient input. There is also opportunity to engage patients throughout the PC CDS research process to ensure that outcome measures are relevant to their needs. Conclusion: Addressing these challenges and embracing these opportunities will help realize the promise of PC CDS—placing patients at the center of the healthcare system.